Dynamic agglomeration effects of foreigners and natives: The role of experience in high-quality sectors, tasks and establishments - Annekatrin Niebuhr; Jan Cornelius Peters; Duncan Roth (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2022)
This paper analyzes how dynamic agglomeration effects differ between foreign and native workers using administrative data on individual employment biographies. According to our results, both groups benefit, on average, equally from gathering work experience in large labor markets. The exception are low-skilled foreign workers, who receive a lower premium for big city experience than low-skilled natives. Providing new evidence on the sources of dynamic agglomeration effects, we show that this difference disappears once we consider the sectors, tasks and establishments, in which foreign and native workers gather experience. More generally, our results indicate that, on average, around 50% of the return of an additional year of experience gained in the densest regions can be ascribed to the acquisition of experience in higher-quality jobs in large cities. – – In diesem Artikel wird auf Grundlage individueller Erwerbsverläufe untersucht, inwiefern sich dynamische Agglomerationseffekte zwischen deutschen und ausländischen Beschäftigten unterscheiden. Unseren Ergebnissen zufolge profitieren beide Personengruppen im Durchschnitt in vergleichbarem Maß von Arbeitserfahrung, die in großen Arbeitsmärkten gesammelt wurde. Eine Ausnahme bilden dabei geringqualifizierte ausländische Beschäftigte, die für Erfahrung aus großen Städten eine geringer Prämie erzielen als vergleichbare deutsche Beschäftigte. Darüber hinaus liefern wir neue Erkenntnisse über die Faktoren, die dynamischen Agglomerationseffekten zugrunde liegen. Werden die Wirtschaftszweige, Berufe und Betriebe berücksichtigt, in denen Beschäftigte ihre Erfahrung sammeln, findet sich kein Unterschied mehr in der Prämie für Erfahrung aus großen Städten zwischen Deutschen und Ausländern. Insgesamt zeigt sich, dass etwa die Hälfte der Prämie, die für Erfahrung in den größten Städten erzielt wird, darauf zurückzuführen ist, dass in diesen Regionen besonders hochwertige Jobs zur Verfügung stehen.
Keywords: J31; J61; R12; R23; 330; Dynamic agglomeration effects; ethnic inequality; job quality; learning; work experience